Associations of circulating apolipoprotein J and myostatin with sarcopenia in older adults with and without type 2 diabetes: a cross-sectional study - Jung, Inha; Shin, Da-Hye; Cho, Hyun Joo; Park, So Young; Lee, Da Young; Yu, Ji Hee; Kim, Nan Hee; Lee, Minjin; Kim, Young-Bum; Seo, Ji A (Frontiers in Endocrinology, 2025)
IntroductionType 2 diabetes mellitus (DM) is a known risk factor for sarcopenia. Apolipoprotein J (ApoJ) and myostatin (MSTN) have been implicated in muscle glucose metabolism. We aimed to examine the association between serum ApoJ and MSTN levels and sarcopenia in older adults, with and without DM.MethodsThis cross-sectional study included 130 community-dwelling adults aged 65–92 years. Serum ApoJ and MSTN levels were measured using ELISA. Sarcopenia was defined as low appendicular skeletal muscle index (ASMI) with low handgrip strength (HS) and/or poor physical performance (PP). Associations were analyzed using age- and sex-adjusted models and logistic regression.ResultsSarcopenia was present in 17.7% of participants. Those with sarcopenia had higher ApoJ levels than those without (p = 0.022). ApoJ levels did not differ by DM status, but MSTN levels were lower in participants with DM (p = 0.012). MSTN levels were positively associated with ASMI, HS, and PP. In logistic regression, ApoJ was independently associated with sarcopenia (OR = 1.027, p = 0.006) and severe sarcopenia (OR = 1.041, p = 0.027), while MSTN was inversely associated with severe sarcopenia (OR = 0.980, p = 0.025). The highest sarcopenia prevalence (26.7%) was observed in the high ApoJ/low MSTN group, and the lowest (0%) in the low ApoJ/high MSTN group.DiscussionElevated ApoJ and reduced MSTN levels are associated with sarcopenia in older adults. These biomarkers may play opposing roles and serve as potential predictors for sarcopenia.